(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This article discusses educational leadership in Yayasan Islam Kelantan (YIK) schools by emphasizing the role of the principle of ‘aqidahas the foundation of Islamic leadership. The study highlights the implementation of the Kelantan Rabbani Education Policy (Dasar Pendidikan Rabbani Kelantan, DPRK), which is based on tauhid (monotheism), and its relationshipwiththedevelopmentofself-efficacyamong school communities.Thediscussion also elaborates on the concept of the tauhid paradigm, the leadership practices of Prophet Muhammad (peace be upon him), and al-Ghazali’s perspectives on educational leadership. Findings show that leadership based on ‘aqidahcan enhance the quality of administration, buildstrongidentityandself efficacyamongteachersandstudents,andnurtureaholisticand excellent educational organization. This study suggests that the principle of ‘aqidahshould continue to be strengthened in educational leadership to ensure the well-being of the ummah in this world and the Hereafter.